Differential prognostic utility of adiposity measures in chronic kidney disease - Cejka, Vladimir; Störk, Stefan; Nadal, Jennifer; Schmid, Matthias; Sommerer, Claudia; Sitter, Thomas; Meiselbach, Heike; Busch, Martin; Schneider, Markus P.; Saritas, Turgay; Schultheiß, Ulla Teresa; Kotsis, Fruzsina; et al. (Journal of renal nutrition, 2023)
Objective - Adipose tissue contributes to adverse outcomes in chronic kidney disease (CKD), but there is uncertainty regarding the prognostic relevance of different adiposity measures. We analyzed the associations of neck circumference (NC), waist circumference (WC), and body mass index (BMI) with clinical outcomes in patients with mild to severe CKD. - Methods - The German Chronic Kidney Disease study is a prospective cohort study, which enrolled Caucasian adults with mild to severe CKD, defined as estimated glomerular filtration rate : 30-60 mL/min/1.73 m2, or >60 mL/min/1.73 m2 in the presence of overt proteinuria. Associations of NC, WC, and BMI with all-cause death, major adverse cardiovascular events (MACE: a composite of nonfatal stroke, nonfatal myocardial infarction, peripheral artery disease intervention, and cardiovascular death), and kidney failure (a composite of dialysis or transplantation) were analyzed using multivariable Cox proportional hazards regression models adjusted for confounders and the Akaike information criteria were calculated. Models included sex interactions with adiposity measures. - Results - A total of 4537 participants (59% male) were included in the analysis. During a 6.5-year follow-up, 339 participants died, 510 experienced MACE, and 341 developed kidney failure. In fully adjusted models, NC was associated with all-cause death in women (hazard ratio 1.080 per cm; 95% CI 1.009-1.155) but not in men. Irrespective of sex, WC was associated with all-cause death (hazard ratio 1.014 per cm; 95% CI 1.005-1.038). NC and WC showed no association with MACE or kidney failure. BMI was not associated with any of the analyzed outcomes. Models of all-cause death, including WC offered the best (lowest) Akaike information criteria. - Conclusion - In Caucasian patients with mild to severe CKD, higher NC (in women) and WC were significantly associated with increased risk of death from any cause but BMI was not.